Crystallinity and magnetic properties dependence on sintering temperature and soaking time of mechanically alloyed nanometer-grain Ni0.5Zn0.5Fe2O4 - Ismayadi Ismail; Mansor Hashim; Idza Riati Ibrahim; Rodziah Nazlan; Fadzidah Binti Mohd Idris; Shamsul Ezzad Shafie; Masni Manap; Ghazaleh Bahmanrokh; Nor Hapishah Abdullah; Wan Norailiana Wan Rahman (Elsevier, 2024)
Indexed by Scopus